A CLOSER LOOK AT VALUE PREMIUM: LITERATURE REVIEW AND SYNTHESIS. (24th September 2015) - Pätäri, Eero; Leivo, Timo
Abstract: This paper provides a systematic review of value premium literature that examines the performance difference between value and growth stocks and the possible reasons for it. We compare and synthesize the results from the different regional stock markets and different sample periods. The literature is categorized according to stock selection criteria that are based on either individual valuation ratios, such as E/P, B/P, D/P, S/P, CF/P, and enterprise value‐based multiples, or composite value criteria that aim to capture more than one dimension of relative value simultaneously or combine them with other classification criteria. We also compare the efficacy of various selection criteria to each other and synthesize the literature on the explanations for the value anomalies. The overall evidence shows that the best criterion varies over time and across the markets. The relative efficacy of different valuation criteria also seems to depend on numerous methodological choices. Recent studies have given mild evidence that combining traditional valuation ratios either with each other or with some financial statement variables could at least in some cases enhance the value premium, although very few studies have provided transparent comparisons between the results based on individual valuation ratios and those based on composite value criteria.